Rangkaian Pengkondisi Sinyal dan Regresi Linier sebagai Metode Peningkatan Akurasi Pembacaan Sensor TDS pada Sistem Hidroponik - Miftah Syahfiqri, Muhammad; Kuswara, Edi; Iqbal Nugraha, Muhammad; Saputra, Zanu (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
Total solidity or TDS is one factor that indicates water quality with PPM readings (parts per million). The TDS role in the hydroponics plantation system is to measure the nutrients contained in the water that is used as a growing medium. However, the TDS sensors used in the hydroponics system are able to read only the PPM value at a sensitivity of 2 PPM per 1 ADC on Arduino Mega or Uno. In the study the authors developed a method of calibration by design a signal condition circuit to increase the value range of TDS censorship output, as well as the application of linear regression methods to obtain the transfer function leading to calibration process. Research shows that a set of op-amps was able to amplifying TDS 'advanced TDS output, which originally had a maximum output of 2.383 v to 5v. The TDS sensor's accurate value that has been added to the signal reinforcement chain that originally valued 96.05% to 96.63%, with an accredited value increase of 0.58%.